(untitled) (GAIMS Journal of Medical Sciences, 2023)
Introduction: Intervertebral disc is a complex structure consisting of highly specialized connective tissue, a combination of hyaline cartilage, fibrocartilage, mucopolysaccharide & dense collagen fibers. Spondylosis or degenerative disc disease of lumbar spine is common musculoskeletal disorder in the elderly people.The prevalence of lumbar spondylosis increases with age also the occurrence of low back pain & disability. Material and Methods: MRI from 50 elderly people ranging from 40 years and above were taken and divided into 4 consecutive groups such as people between 40 to 50, 50 to 60, 60 to 70 & above 70 years. The rate of degeneration was graded into grade-0,1,2,3 for normal, mild, moderate, and severe respectively. The MRI were assessed for presence of lumbar disc degeneration. The observations were noted and statistical analysis was done. Results: Demographic profile of study subjects shows that degeneration was more common problem among female compared to male and there was no much variation in relation to age distribution of study subjects A total of 50 subjects 40years and above were enrolled & divided into 4 consecutive groups such as people between 40 to 50, 50 to 60, 60 to 70 years (mean; 55.01± 10.33 years) Grades of lumbar degeneration were correlated with decadal age. Severity of degeneration was proportionately increasing with the increasing age Conclusion: Lumbar disc degeneration was highly prevalent with age. Education on life style modification should be implement for health promotion and primary prevention